Do assistencialismo à intervenção social: o voluntariado na construção de agências - Lage, Marisol Patrícia Saucedo Revollo (2019)
Schools have increasingly invested in repertoire, technologies and the provision of language teaching as a way to meet families' quest for academic excellence in order to prepare their children for an increasingly competitive market. However, it is perceived that what this investment brings is not enough to deal with an increasingly excluding globalized world. To overcome this context, this study had the general objective of investigating the process of construction of the agency of students participating in a volunteer course proposed in the free period of a bilingual Spanish and Portuguese school in the city of São Paulo. The elaborated proposals were developed based on the Socio-Historical-Cultural Activity Theory- Social Activity. This study is based on the interdisciplinary character of Applied Linguistics because it seeks important reflections on the context and the social practice of language in the process of teaching-learning. Methodologically, the study presents itself as a Collaborative Critical Investigation. It has as assumption the interference in the context, transcending the observation and the description. The research questions are: 1) What types of agencies are built in the educational volunteer course? 2) How are they constructed? The analysis corpus was composed of recordings of videos and audios, as well as written documents about the tasks elaborated by the group. The data were analyzed according to the enunciative, discursive, linguistic, and multimodal categories and allowed the analysis of the manifestations of the contradictions and the decisions experienced by the participants involved. The analysis of the excerpts shows that the experienced encounters intensified the relations between the members, while the challenges achieved allowed the expansion of repertoire in the construction of agencies: critical-collaborative, relational, decapsulation and transformative activist. In this way, it was possible to analyze the construction of new ways of acting that enabled to redefine the life of society in school and school in society